Optimization of training loads at the pre-competition stage of preparation in cyclic sports - Panchenko I.A.; Grigoriev V.I.; Novitsky Ya.I.; Yakovlev S.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to increase the efficiency of pre-competition preparation management in cyclic sports based on optimizing the ratio of special loads. Methods and structure of the study. An analysis of the ratio of special loads was carried out, ensuring the attainment of peak sports form. The testing involved 48 athletes, men aged 18-20 years, 16 middle-distance runners, 18 kayakers and 14 freestyle swimmers. 41% of the subjects are masters of sports (MS) and 59% are candidate masters of sports. An information and analytical platform has been developed that allows monitoring changes in mechanical productivity, biodynamic parameters and oxygen transport functions. Results and conclusions. At this stage, an increase in competitive speed and an improvement in functional state is achieved by optimizing the tempo SR, the length of the “step” SL, the rhythm R, and the power WR. The effectiveness of the regulator is confirmed by a statistically significant improvement in results in rowing K-1 1000 m, running at a distance of 800 m and swimming at a distance of 200 m h/s.